RANCANG BANGUN SMART GREENHOUSE UNTUK BUDIDAYA TANAMAN SAWI PAKCOY (brassica rapa subsp) BERBASIS ANDROID - Thomas Nelson Kolo; Lusianus Bala; Oktavia Prima Bili; Yudit Oviana Berek; Bernadeta Novia W. R. Mau; Maria Erlina Naben; Darsono Nababan; Yoseph P. K. Kelen (Universitas Methodist Indonesia, 2023)
Due to rising market demand, green mustard cultivation is still being developed. A soil temperature and humidity control system based on the Arduino Uno microcontroller will be designed and tested in this study, as will an automatic plant watering system for this control. The part for recognizing temperature and mugginess utilized is the DHT22 sensor with a result as a computerized signal and has 4 pins comprising of a power supply, information sign, invalid and ground. This study employed engineering design for the production of the automation system. The study produced a smart greenhouse that is capable of remotely controlling microcontroller equipment and monitoring devices like sensors and can regulate, adjust, and modify the climate to optimize the conditions and processes of plant growth in the greenhouse.